Temporal trends in childhood cancer survival in Egypt, 2007 to 2017: A large retrospective study of 14 808 children with cancer from the Children's Cancer Hospital Egypt. Issue 7 (15th October 2020) - Soliman, Ranin M.; Elhaddad, Alaa; Oke, Jason; Eweida, Wael; Sidhom, Iman; Ahmed, Sonia; Abdelrahman, Hany; Moussa, Emad; Fawzy, Mohamed; Zamzam, Manal; Zekri, Wael; Hafez, Hanafy; et al.
Abstract: Childhood cancer is a priority in Egypt due to large numbers of children with cancer, suboptimal care and insufficient resources. It is difficult to evaluate progress in survival because of paucity of data in National Cancer Registry. In this study, we studied survival rates and trends in survival of the largest available cohort of children with cancer (n = 15 779, aged 0‐18 years) from Egypt between 2007 and 2017, treated at Children's Cancer Hospital Egypt‐(CCHE), representing 40% to 50% of all childhood cancers across Egypt. We estimated 5‐year overall survival (OS) for 14 808 eligible patients using Kaplan‐Meier method, and determined survival trends using Cox regression by single year of diagnosis and by diagnosis periods. We compared age‐standardized rates to international benchmarks in England and the United States, identified cancers with inferior survival and provided recommendations for improvement. Five‐year OS was 72.1% (95% CI 71.3‐72.9) for all cancers combined, and survival trends increased significantly by single year of diagnosis ( P < .001) and by calendar periods from 69.6% to 74.2% ( P < .0001) between 2007‐2012 and 2013‐2017. Survival trends improved significantly for leukemias, lymphomas, CNS tumors, neuroblastoma, hepatoblastoma and Ewing Sarcoma. Survival was significantly lower by 9% and 11.2% ( P < .001) than England and the United States, respectively. Significantly inferior survival was observed for the majority of cancers. Although survival trends are improving for childhood cancers in Egypt/CCHE, survival is still inferior in high‐income countries. We provide evidence‐based recommendations to improve survival in Egypt by reflecting on current obstacles in care, with further implications on practice and policy. Abstract : What's new? While childhood cancers are a priority in most countries, it is not always clear whether survival rates are improving, nor what types of barriers might impede care in low‐and‐middle‐income countries (LMICs). In this Egyptian study, the authors determined overall survival (OS) for almost 15, 000 children, and identified specific cancers with inferior survival. They then found that OS was lower in Egypt than in England and the U.S., and developed recommendations for improving care based on current real‐world evidence, including factors such as delayed diagnosis and increased risk of infection.